Germination and Storage of Dyera Costulata Hook. F. and Macaranga Gigantea Mull. Seeds - Sao, Chanthol (2004)
Good physiological quality of seed such as high germination percentage and vigor are the most important factors to be considered in the production of high quality tree seeds for commercial plantations. This study therefore was undertaken with the main objective of enhancing the germination and storage condition of commercially important tree seeds, Dyera costulata Hook.f. and Macaranga gigantea Mull. This study also envisioned of developing tetrazolium test for rapid detection of seed viability. Several germination media such as paper, sand, soil, forest soil, coconut husk and paddy husk were tested for best germination. Whereas, three different storage conditions (refrigerated i.e 10 and 20ºC and ambient i.e 30ºC) and different storage periods (0, 31, 89 and 181 days); three different plant growth hormones (GA3, BAP and kinetin) at four different concentrations (0.1, 0.2, 0.5 and 10 mg/l) were used to determine the best conditions for storage and growth promoter for both D. costulata and M. gigantea seeds. In addition, three different germination media (sand, soil and forest soil) and light regimes (25%, 55% and 75% relative light intensity) were tested to find out the best condition for seedlings growth. The results of the study indicated that the best germination media for both tree seeds was the sand, followed by forest soil and soil. This study also revealed that the best temperature for storage was at 20oC giving from 85 to 97% seed viability. However,storage of more than 89 days tends to reduce the germination rate when stored at 10oC, and 20oC, and more 30 days if stored at 30ºC. Meanwhile, among the three types of hormones it was found that GA3 at 10mg/l was most effective not only on the germination but also on excised seedcoat. While, among the concentrations used 10mg/l gave an overall best result for all the hormones in enhancing the germination process. On the other hand, it was found that seedlings grow best when planted in forest-soil and provided with 25% light intensities. Through tetrazolium test only 57% viability was gained for M. gigantea seeds as compared to the control test which resulted to 40% viability. Whereas, the viability of seeds was estimated at 93% compared to the control test, which resulted only to 87.5% viability for D. costulata seeds. However, the daily germination percentage was inconsistent, making the germination period longer for those seeds sown in coconut husk and paddy husk as compared to sand and soil treatments. It was found that buried seeds produced better germination rate that resulted vigour seedlings as compared to freshly collected seeds. Overall, hormone treatment using GA3, BAP and Kinetin at various concentrations was found to enhance the germination rates of M. gigantea seeds. However, it was found that GA3 at 10mg/l was better treatment for germination that gave 65%, even when combined with excised seedcoat that gave 74% viability. From the study upon various media and light intensities, it was found growth was significantly better at 75% light in forest-soil condition. Comparison of the anatomical structures of buried seeds and fresh seeds of M. gigantea were carried out using scanning electron microscopy (SEM). Studies indicated that the buried seeds had a thinner pericarp, full endosperm and had a better-developed embryonic axis compared to the fresh seeds. Differences in buried seeds and fresh seeds were evident their pericarp thickness, between, i.e. 357.6μm and 308.7μm respectively. Differences were also evident within the radicle area where structures from fresh seeds were not as well organized as those of buried seeds